RESEARCH AND DESIGN OF MULTI-DIRECTIONAL DUMPING CONSTRUCTION IN TRUCKS - Thong Duc HONG; Hiep Thanh THAI (Scientific Journal of Silesian University of Technology. Series Transport)
In the current transportation industry, especially transporting coal, sand, heavy stone, construction waste, etc., dump trucks occupy a critical position. Most traditional dump trucks can only dump goods vertically, so their manoeuvrability is not high. Especially in tight spaces such as construction sites, it causes many difficulties for loading and unloading traditional dump trucks, which takes a lot of time and effort for the driver. In this paper, we have mainly focused on solving the above difficulties. Hence a multi-dimensional dump truck model was designed. The hydraulic motor actuated by the directional valve rotates the container on the required side. This design aims to improve the features and performance of dump trucks compared to existing conventional vehicles. This concept will save operating costs & energy consumption, which leads to increased efficient working. In this study, the dump truck can rotate 1800 in both directions through a hydraulic motor and gearbox linked with slewing bearing.